مشكلة الجهل بالآخَر وأثرها في إعاقة التنمية المستدامة (Journal of the College of Basic Education, 2026)
The research addresses the problem of ignorance of the other as an intellectual and social dilemma that has plagued human societies throughout the ages. It takes into account its multiplying impact in culturally and religiously mixed societies, resulting from misunderstandings, escalating conflicts, and the disruption of development. It aims to advocate for building a culture of knowledge of the other within Islamic society, in light of the global trend toward achieving the 2030 Sustainable Development Goals. It has become necessary to reconsider the relationship between knowledge of the other and the building of cohesive and peaceful societies. To what extent does ignorance of the other contribute to disrupting sustainable development projects in Muslim societies? In response to this problem, the research is organized into an introduction, five chapters, a conclusion, and an index of sources and references, according to the descriptive-analytical method.He concluded with the following conclusions:Ignorance of the Other represents a major obstacle to achieving sustainable development in Muslim societies. Addressing this ignorance begins with supporting harmonious educational curricula, promoting the values ​​of dialogue, appreciating diversity, and valuing diverse religious experiences rather than demonizing them.Ignorance of the Other breeds misunderstandings and exclusionary judgments, results in fanaticism, and fuels division and discord. The call remains open to intellectual and scientific elites to adopt reformist knowledge projects that raise the nation's awareness of the diverse Other, viewing them as partners in shaping the future, rather than as enemies to be feared.Sayyed Ali Al-Amin's efforts provide a practical model for overcoming ignorance of the other, revealing that cognitive correction of inter-sectarian relations is a key pillar for building stable nations capable of economic and social advancement, in a manner fully consistent with the goals of sustainable development in our societies.